Transnational policing and sex trafficking in southeast Europe: policing the imperialist chain - Papanicolaou, Georgios (Transnational crime, crime control and security, 2011)
"Mounting a vigorous critique on existing approaches to transnational policing, this book lays out an argument situating transnational policing within contemporary transformations of the capitalist state and imperialism, looking at the particular case of regional police cooperation against sex trafficking in Southeast Europe"--